PENGARUH PENAMBAHAHAN PARTIKEL MAGNETIK Fe 3 O 4 TERHADAP PENINGKATAN KONDUKTIVITAS MEMBRAN POLIMER ELEKTROLIT (PVA – LiOH) - Rahmawati M (PROSIDING SEMINAR KIMIA, 2013)
Electrical conductivity of electrolyte polymer PVA.LiOH with nanoparticle Fe 3 O 4 dispersion result show a significant increase when compared to electrolyte polymer without nanoparticle Fe 3 O 4 . The electrolyte polymer PVA.LiOH electrical conductivity with nanoparticle Fe 3 O 4 reach 1,18 x 10 -3 Scm -1 orde, while without nanoparticle Fe 3 O 4 the electrical conductivity reach 2,48 x 10 -4 Scm -1 orde. This indicates an increase of amorphous phase after magnetic particle Fe 3 O 4 addition. The existence of magnetic nanoparticle Fe 3 O 4 can effectively increase the amorphous fraction of electrolyte polymer PVA.LiOH and magnetic properties carried by Fe 3 O 4 a new potential in development of electrolyte polymer.